Nasal and cutaneous mucormycosis in two patients with lymphoma after chemotherapy and target therapy: Early detection by metagenomic next-generation sequencing - Zhang, Qing; Liu, Xingchen; Liu, Yanyan; Wang, Huiqin; Zhao, Ran; Lv, Xiaodong; Wei, Xudong; Zhou, KeShu (Frontiers in Cellular and Infection Microbiology, 2022)
Mucormycosis is a conditionally pathogenic fungal disease with high morbidity that mainly affects patients with decreased immunity. Diagnosis relies on the histopathological examination of microorganisms with the typical structure of mucormycetes in tissues and subsequent confirmation via culture. Early detection of causative microorganisms is critical to rapidly administer appropriately targeted antibiotics. Metagenomic next-generation sequencing (mNGS) is an innovative and sensitive technique used to identify pathogenic strains. Here we used mNGS to timely diagnose an infection with Lichtheimia ramosa and Mucor irregularis in two patients with hematologic malignancies; the infections manifested as nasal and cutaneous infections and developed after chemotherapy and small molecule targeted therapy. Following treatment with amphotericin B cholesteryl sulfate complex, the symptoms were reduced significantly, and both patients obtained successful outcomes. Additionally, we searched and summarized the current medical literature on the successful diagnosis of mucormycosis using mNGS. These cases indicated that mNGS, a novel culture-independent method, is capable of rapid, sensitive, and accurate identification of pathogens. mNGS may be a complementary method for the early identification of mucormycosis, allowing for appropriate and timely antibiotic administration and thus improving patient outcomes.